Equatorial ionospheric plasma drifts velocities using radar observations (BIBECHANA, 2016)
This study presents the experimental results of the equatorial ionospheric plasma drift zonal velocity obtained from Incoherent Scatter Radar (ISR) observations for 6 selective days in 2011 from Jicamarca, Peru. Our results indicate that the daytime drifts are westward with peak values mostly below ~50 m/s, while the night time drifts velocities are eastward, with a maximum value up to 120 m/s at around local midnight hours. The drift velocity decreases during post-midnight hours and starts to reverse westward in early morning hours. Our plasma drifts results are in good agreement with results from previous radar studies and other measurement techniques. BIBECHANA 14 (2017)1-8